ISOLASI Actinomycetes ENDOFIT DARI TANAMAN AKAR WANGI (Vetiveria zizanioides) DAN UJI AKTIVITAS SENYAWA ANTIBAKTERI TERHADAP Staphylococcus aureus DAN Escherichia coli - - Elsie; Nofripa Herlina; Ruli Tias Putri (LPPM Universitas Muhammadiyah Riau, 2018)
Actinomycetes endophytes are bacteria that live in plant tissues and are known as secondary metabolites that have activity as an antibacterial. This study was conducted to isolate Actinomycetes endophytes from vetiver plant tissue (Vetiveria zizanioides) and test for the activity of antibacterial compounds againstStaphylococcus aureus and Escherichia coli by using diffusion method. Actinomycetes endophytes successfully isolated were isolates of RTP-1, RTP-2 and RTP-3. The results of antibacterial compound activity test showed that the three Actinomycetes endophytic isolates were able to inhibit the growth of S. aureus and E. coli bacteria. The best inhibitory ability against E. coli bacteria with a drag zone diameter of 20 mm while the largest inhibitory zone diameter against S. aureus bacteria was 9 mm.